Photosynthetic and physiological responses of different peony cultivars to high temperature - Ji, Wen; Hong, Erman; Chen, Xia; Li, Zhijun; Lin, Bangyu; Xia, Xuanze; Li, Tianyao; Song, Xinzhang; Jin, Songheng; Zhu, Xiangtao (Frontiers in Plant Science, 2022)
In order to investigate the cause of the difference in heat tolerance between different peony varieties ('Lu He Hong' and 'Zhi Hong'), the physiological response of peony varieties to the disorder of photosynthesis caused by high temperature was studied. The photosynthetic characteristics and regulation mechanism of leaves of two peony cultivars under high temperature were studied. The changes of photosynthetic parameters of peony under high temperature were recorded by photosynthetic apparatus. Chlorophyll a(Chla) fluorescence transient was recorded by plant efficiency analyzer (PEA) and analyzed by JIP test (O-J-I-P fluorescence transient analysis). Several parameters were derived to explain the differences of photosynthetic efficiency among different peony varieties. The experimental varieties responded differently to the investigation conditions. PCA analysis showed that 'fat red' had stronger tolerance and PSII had better thermal stability. The reduced efficiency of the 'Lu He Hong' PSII antenna results in higher heat dissipation value and increases in light energy absorbed per unit reaction center (ABS/RC), energy captured per unit reaction center for QA reduction (TR0/RC), and energy dissipated per unit reaction center (DI0/RC), which significantly results in lower total photosynthetic performance (PItotal). The light capture complex of 'Zhi Hong' had higher connectivity with its reaction center, less damage to oxygen-evolving complex (OEC) activity, and better stability of PSII system. The results obtained in this study may be applicable to peony breeding programs, especially for the selection of peony varieties that are more tolerant and resistant to high temperature.